Improving Teachers ICT Application Competencies: A Case Study at Vocational High School in East Kalimantan Province - Saiful Ghozi; Risty Jayanti Yuniar; Sara Wibawaning Respati (Southeast Asian Mathematics Education Journal, 2017)
Innovation in learning should be done in line with information and computer technology (ICT) literacy development for both students and teachers. One of the problems with learning using ICT is the differences in competency of teachers in a small city due to the lack of access to its development. This study is a qualitative research based on a community service activity to enhance ICT application competencies of mathematics teachers in vocational high school in Penajam Paser Utara (PPU) district, East Kalimantan Province(Indonesia), utilizing GeoGebra and Autograph™. This study consisted of five phases: (1) situation analysis, (2) training and workshops for GeoGebra and Autograph™ utilization, (3) implementation of lesson study (LS), (4) data analysis and presentation, and (5) discussion. The results of this study are: (1) students became more motivated to learn mathematics by using GeoGebra, (2) teachers found that GeoGebra can develop students’understanding of mathematics concepts easier, and (3) ICT competencies in teaching in vocational high school in PPU, especially in the utilization of GeoGebra and Autograph™, increased. The recommendation is that LS should be continued to improve the effectiveness of GeoGebra and Autograph™ utilization in other mathematics topics. A much larger studywould be needed to determine if the results of this research are due to the approach or due to the teachers’ enthusiasm, novelty effect or what is known as the Hawthorne Effect.